Is the CO2 emissions reduction from scale change, structural change or technology change? Evidence from non-metallic sector of 11 major economies in 1995–2009. (1st April 2017) - Wang, Jin-Wei; Liao, Hua; Tang, Bao-Jun; Ke, Ruo-Yu; Wei, Yi-Ming
Abstract: The contribution of non-metallic sector to global CO2 emissions is increasing. However, there are very few studies on non-metallic sector CO2 emissions from international comparative perspective. This paper proposes an integrated model employing LMDI (Logarithmic Mean Divisia Index) decomposition technique and TOPSIS (the Technique for Order Preference by Similarity to Ideal Solution) method to contribute to the existing literature by filling the gap that the drivers of aggregate and national level non-metallic sector CO2 emissions and its impacts on CO2 emissions reduction have not been estimated by relevant models. First, we analyze drivers of non-metallic sector CO2 emissions in BRIC countries and G7 countries using LMDI decomposition method. Second, we evaluate the low-carbon development of non-metallic sector in the 11 major economies from a comprehensive viewpoint of main drivers using TOPSIS assessment model. Finally, based on the results of the model, this paper presents some implications for the non-metallic sector CO2 emissions reduction and low-carbon development. Highlights: Regional structural change plays a significant role in CO2 emissions fluctuation on the aggregate level. Scale effect is a main driver accountable for the CO2 emissions fluctuation to the underperforming countries. CO2 emissions reduction to the well-performing countries can be categorized in three patterns.